Caribbean offshore Financial Centers : Past, Present, and Possibilities for the Future - Suss, Esther (IMF Working Papers; Working Paper ;, 2002)
The paper reviews the development of offshore financial activities in the English-speaking Caribbean islands and takes stock of the size and status of these sectors today. In view of the heightened concerns of the international community about money laundering, the costs and risks to countries of having or establishing offshore sectors have risen considerably.